Spatial and Temporal Monitoring of North African Turtle Doves Streptopelia turtur arenicola (Hartert, EJO, 1894): First Migrants Arrive Early and Select Nesting Trees next to Foraging Resources while Second Breeders’ Wave Breed around Earlier Nests - Mounir, Mohamed; Mansouri, Ismail; Squalli, Wafae; Hammada, Soumaya; Dakki, Mohamed (International Journal of Zoology, 2023)
This study aimed to evaluate the spatial microdistribution and temporal microdistribution of the North African subspecies of the globally threatened Turtle Doves in Morocco. From the end of February to early September, we monitored the migration dates, counting arrival and departure dates, and breeding chronology, to clarify if the breeding season is divided into sub-breeding phases or not. Equally, the spatial distribution of nests following potential breeding phases was surveyed weekly in Beni Mellal province following a map of a selected orange orchard. Doves arrived in Beni Mellal in the third week of March and left in mid-October, according to the results. The first nests occurred in the second week of April, followed by the first eggs in the third week of April and the first chicks in the first week of May. PCA analysis showed that the nesting and laying stages were achieved principally during the last two weeks of April and the first three weeks of May, the hatching stage between the fourth week of May and the second week of July, and fledging between the fourth week of July and the first week of September. Further, the breeding season was divided into two phases: the first breeding phase, from the first week of April to the first week of June, and the second phase, between the second week of June and the second week of August. The DCA analysis and orchard-created map indicated that the first wave of breeders colonized the marginal trees located on the orchard sides, surrounded by foraging cereals and legumes, and the second breeding-phase nests were constructed in flocks next to the nests of the first breeding phase. According to this strategy, the first breeders prospect the orchard and select nesting trees near foraging resources, while the second breeders’ wave colonizes trees near successfully used prospector sites. These findings are of great importance for comparative investigations and habitat-scale conservation management.